Evaluación del comportamiento agronómico de líneas promisorias y la variedad de triticale (x Triticosecale Wittmack) del INIAP bajo las condiciones agroecológicas del campus Salache UTC 2021-2022. - Lozada Hidalgo, Betzy Mishell (2022)
The production of wheat and rye in Ecuador is lower than the volumes that the country demands of these cereals; despite the multiple advantages that triticale presents compared to its parents, farmers prefer traditional grains. It is estimated that around 70% of farmers are dedicated to the cultivation of wheat and barley. This investigation was carried out at the Technical University of Cotopaxi - Salache Campus, Eloy Alfaro Parish, Latacunga Canton, Cotopaxi Province, to evaluate the agronomic behavior of the promising lines of triticale (x Triticosecale Wittmack) under the conditions of the investigated site so, it was proposed to determine the adaptation and yields of the promising lines and the variety in the study area. A completely randomized block design (DBCA) with five treatments and three repetitions was proposed, resulting in 15 experimental units. The variables evaluated were: emergence percentage, plant vigor, growth habit, days to spike, plant height, straw type, spike size, number and weight of grains per spike, yield, test weight, the weight of 100 grains type, and color of grain and reaction to diseases based on Manual No. 111 of Evaluation and Selection Parameters in Cereals published by the National Institute of Agricultural Research (INIAP) based on the Zadoks scales. For the data analysis, a statistical analysis of normality (Modified Shapiro Wilks) was carried out; on the sources of variation that indicated statistical significance at the 5% Tukey test. For the variables that were evaluated employing scales, tables of averages were generated, as well as for those that did not show statistical significance. It was determined that all treatments were adapted to the conditions of the field under study; the treatment with the best adaptability to agroecological conditions was the promising line TCL-10-004 because it was superior in 9 of 17 variables evaluated, in addition to presenting the best yield with 12810.46 kg ha-1 followed by the promising line TCL-10-001 with a yield of 11701.65 kg ha-1, unlike the Triticale 2000 variety whose yield was lower with 9793.37 kg ha-1. It is concluded that the promising line for the study area is TCL-10-004, so it is recommended to continue investigating this line and other plant materials from INIAP.